Pengaruh Penggunaan Model Contextual Teaching and Learning (CTL) Terhadap Motivasi Belajar Pendidikan Agama Kristen Siswa Kelas VIII SMP Negeri 3 Lintongnihuta Kabupaten Humbang Hasundutan Tahun Pembelajaran 2022/2023 - Armela Nababan; Senida Harefa; Robinhot Sihombing (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2023)
The aim of this research is to determine the positive and significant influence of the use of the Contextual Teaching and Learning Model on the Learning Motivation of Christian Religious Education in class VIII of SMP Negeri 3 Lintongnihuta, Humbang Hasundutan district, for the 2022/2023 academic year. The method used in this research is descriptive quantitative, with a population of all class VIII students at SMP Negeri 3 Lintongnihuta for the 2022/2023 academic year, totaling 191 people and a sample of 48 people, which is 25% of the total population. Data was collected using a closed questionnaire of 37 items, of which 19 questionnaire items were for variable X and 18 questionnaire items were for variable Y which were compiled by the author based on variable indicators according to expert theory. 1) Results of data analysis: a) positive relationship test obtained by the value rxy = 0.585 > rtable(a=0.05,n=48) = 0.284, thus it is known that there is a positive relationship between variable X and variable Y. b) Test The significant relationship obtained is the value tcount= 4.889 > ttable(a=0.05,dk=n-2=46)= 2.021, thus there is a significant relationship between variable X and variable Y. 2) Test the influence: a) Test the regression equation , the regression equation Y ̂=